SOCIO-ECONOMIC STUDY ON THE THREATS AND EFFECTS OF CLIMATE CHANGE ON LOCAL LIVELIHOOD IN SELECTED DISTRICTS OF THE NORTHERN REGION OF GHANA - Amoako, E. E.; Donkoh, S. A.; Ansah, I. G. K. (UDS International Journal of Development, 2017)
The Northern Sector Action Awareness Centre (NORSAAC), a local NGO in Northern Ghana commissioned a research into the threats and effects of climate change on local livelihoods of the local people, especially women and the youth in four districts of their operational area in the northern region of Ghana. In all, 320 respondents (160 males and 160 females) were selected for interview using the stratified and random sampling techniques. The method of data analysis was basically descriptive. We found that the peopleâ€™s livelihoods basically centre on small-scale agriculture and its related activities such as food processing (using traditional methods) and petty trading, especially for the women. Limited opportunities such as education, off-farm activities and credit as well as irrigation and extension services have meant that they are not able to cope with the negative effects of climate change. Consequently, while a significant percentage of respondents relied on prayers and sacrifices to cope with the effects of climate change, others were simply doing nothing. As intervention measures we propose irrigation and some improved, but affordable equipment for food processing. Also, efforts must be stepped up to increase access to education, credit and extension services in the district, especially for women. Keywords: Climate change, Livelihoods, NORSAAC, Northern GhanaÂ